Meningkatkan Motivasi Belajar Siswa Melalui Metode PBL Materi Kisah Pembebasan Bangsa Israel Pak Kelas IV SDN 08 Buluh Merindu - Iskandar Iskandar (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The background of this research is the low learning motivation of students at SDN 08 Buluh Merindu. Research Method Using Quantitative The results of the Cycle 1 research showed that students' success rate in understanding the material was 79%. However, only 40% of students reached the new skill level, 50% of students were at the proficient level, and 10% of students were at the adequate level. In cycle 2, research data shows that student learning motivation has reached the set target of 79%. In terms of achieving skill levels, 60% of students are at the advanced level, 30% of students are at the proficient level, and only 10% of students are at the adequate level. The application of the Problem Based Learning (PBL) method in Catholic Religious Education lessons has been proven to improve student learning outcomes and motivation. The implication of these findings is that the Problem Based Learning (PBL) learning model has been proven to be able to increase student learning motivation in the classroom.